CLASSROOM MANAGEMENT IN CROSS – CULTURAL CONTEXT - Iļjina, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The subject to be discussed in the present article is classroom management in cross-cultural context. The main reason for the choice of this particular choice was determined mostly by the necessity of varying English language teachers’ management skills and teaching techniques in a mixed linguistic classroom. The aim of the research is to explore the ways of improving classroom management skills in a cross-cultural context.